2020
DOI: 10.1002/ana.25885
|View full text |Cite
|
Sign up to set email alerts
|

Plasma NT1 Tau is a Specific and Early Marker of Alzheimer's Disease

Abstract: Objective There is an urgent need for sensitive, widely available, blood‐based screening tests to identify presymptomatic individuals destined to develop Alzheimer's disease (AD). We investigated whether tau detected in plasma by our in‐house NT1 assay is specifically altered in AD, and when applied to patients with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) can serve to predict progression to AD dementia. The predictive value of NT1 versus tau measured using assays from Quanterix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…83 The core AD CSF biomarkers (Ab 42 , phospho-tau, total-tau) enabled the quantification of these pathological processes supporting the diagnosis of AD. 83,84 However, the complexity of the blood matrix, peripheral sources, and protein degradation have hampered the translation of this biomarker panel in the blood, 84,85 although new assays for tau and phosphotau are being investigated. 85,86 The pathological process of AD begins years before symptoms are manifest.…”
Section: Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…83 The core AD CSF biomarkers (Ab 42 , phospho-tau, total-tau) enabled the quantification of these pathological processes supporting the diagnosis of AD. 83,84 However, the complexity of the blood matrix, peripheral sources, and protein degradation have hampered the translation of this biomarker panel in the blood, 84,85 although new assays for tau and phosphotau are being investigated. 85,86 The pathological process of AD begins years before symptoms are manifest.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…83,84 However, the complexity of the blood matrix, peripheral sources, and protein degradation have hampered the translation of this biomarker panel in the blood, 84,85 although new assays for tau and phosphotau are being investigated. 85,86 The pathological process of AD begins years before symptoms are manifest. 83 Thus, a biomarker that facilitates early detection of the disease would enable early treatment and better prognosis for AD patients with familial AD.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Plasma t-tau has also been investigated widely in AD [25,29,30], yet these studies have concluded that plasma t-tau, certainly in its current immunoassay format, only shows minor changes with large overlaps with disease controls to have clinical relevance for AD. Recent studies, despite being preliminary, have suggested that associations with AD can be achieved by measuring t-tau using an assay format directed toward the N-terminal region of the tau protein in blood [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on fluid-based biomarkers with a N-terminal assay (NT1)—including the N-terminal mAbTau12 (amino acids 6– 13)—show that as NT1 levels increase, clinical decline in subjects with positivity for other AD biomarkers worsens. NT1 levels probably remain intact in non-AD dementia [3638]. Supported by our quantitative neuropathological results and the success of other N-terminal truncated assays, mAbD13 may become an essential player in the arsenal of biofluid biomarkers against AD.…”
Section: Discussionmentioning
confidence: 97%